An examination of the different experiences and emotions (positive and negative) of healthcare providers dealing with COVID-19-infected or suspected cases in Ilam (2020) - Nasim Bozorgi; Zolaykha Karamelahi; Iraj Ahmadi; Reza Valizadeh; Aylin Bozorgi; Aliashraf Mozafari (Shahrekord University of Medical Sciences, 2024)
Background and aims: The COVID-19 pandemic emerged in late 2019 with increased infection and mortality rates. Even with observing safety measures, medical staff have to deal with a high level of mental and physical pressure during an epidemic, and they might demonstrate diverse behaviors rooted in their experiences and emotions toward the situation. The paper examines different experiences and emotions of medical staff dealing with COVID-19 in Ilam, Iran. Methods: A cross-sectional study was carried out with the participation of 200 care providers in 2020. Data was gathered using two questionnaires: the scale of positive and negative emotions (SPANE) and the positive and negative affect scale (PANAS). Data analyses were done in STATA12 using linear regression models. Results: The mean score of positive emotion in ICU, general, maternity, and administrative wards in women were 32±6.23, 34.07±6.74, 35.35±9.24, and 35.61±6.91 respectively. The mean scores of Negative emotions in the Maternity ward and administrative departments were higher than in the ICU and CCU wards (P=0.05). The midwives' mean negative emotions score was lower than the physician's (P value<0.05). Average levels increased by about 4.41 scores in negative experiences for individuals with a work experience higher than 25 years compared to those with work experience less than ten years (P=0.03). Conclusion: Factors such as type of work, workplace, and work experience that affect care providers' positive and negative experiences and emotions should be considered in staffing arrangements and their expectations.